THE ROLE OF SELF ACCEPTANCE ON THE MENTAL HEALTH OF ADOLESCENT IN THE PANDEMIC - Nuraini Hasna Hamidah (Study Program Guidance and Counseling, Univesitas Pendidik, 2022)
The living conditions since the COVID-19 pandemic have changed a lot of people's lives. Changes that occur suddenly, make it difficult for people to adapt and cause stress to trauma. Adolescents are one of the groups that are vulnerable to experiencing psychological impacts and mental health disorders during a pandemic because the psychological conditions of adolescents are still vulnerable, filled with conflict because of the many changes they face. This article tries to analyze the role of self-acceptance on mental health in adolescents during a pandemic by using the literature study method. If the teenager has accepted that the current condition is not a normal condition, then the teenager will be ready to adapt. So, if a teenager is able to accept himself and his current condition, he will be able to think positively and be mentally healthy.